School and Social Educational Vulnerability in Chile: Experiences and Preparedness of Novice Teachers of English - Romero-Villarroel, G (Routledge, 2024)
Drawing on Sen’s notion of social justice in the Capability Approach, this paper examines the experiences of a group of novice teachers from English teacher education programmes working in marginalised schools in Chile. Through open-ended surveys and interviews, I investigated how new teachers navigate their first teaching years in contexts of educational vulnerability, how they perceive their teacher education programs and preparation to work in such school contexts, and how they balance the interplay between unfreedoms and the exercise of freedoms to teach students at social risk. The findings reveal the impact of contextless English teacher education programs and how these trigger future teacher motivation to develop a deeper understanding of educational vulnerability and their freedom to move away from language teaching issues to accommodate their teaching based on their care and commitment to their students. This paper closes by making a call for the importance of a grassroots approach in the development of English teacher education programs designed with members of marginalised communities. © 2022 Informa UK Limited, trading as Taylor & Francis Group.